The Use Of RAP (Read Ask Paraphrase) Strategy To Increase Students’ Reading Comprehension Of The Eight Grade Students Of SMAN 3 Kota Bima In Academic Year 2017/2018 - Fitri Ningsi; Indri Raodatul Jannah (STKIP Taman Siswa Bima, 2018)
The objective of the study is to increase students’ reading comprehension at eight grade of SMA N 3 Kota Bima in academic year 2017/2018 through RAP (read ask paraphrase) strategy. The research designed was Classroom Action Research which has four procedures, namely: Planning, Implementing, Observing, and Reflecting. The subjects in this research were the eight grade which has 30 students consisting of 13 males and 17 females students. The researcher used two kinds of research instruments, namely: Observation sheet and Speaking test. This research applied in two cycles. The data shown that both of teacher and students activities were in active level the students’ speaking skill, based on the result observation data gained mean score class of first cycle were 73 and total of students were fulfil the criteria of individual only 17 from 30 students, so that, precentage of learning result were 56%. It means that the research was unsuccessful because the target of the success in this study was 85% among the whole member of the students. So, the researcher should arrange for the second cycle, after doing improvement in second cycle the result of observation data gained mean score of the class were 86 and total of students were fulfill the criteria of individual 27 from 30 students, so that, percentage of learning result were 90%. It means that the application of the RAP is suitable to increase students’ speaking skill.